An address delivered before the Alumni Association of Nassau Hall, on the date of the Annual Commencement of the College, Sept. 25, 1833, by John Sergeant, LL. D. - Anonymous, Anonymous (Analecta Gorgiana, 2010)
The article comments on and reprints passages from a commencement speech for the Alumni Association of Nassau Hall. In the address, John Sergeant discusses why not many students are inadequately prepared for college work